Integration of moocs as blended learning in learning research methodology course - Mohd. Yusof, Sanitah (UTM, 2016)
As part of the New Academia Learning Innovation (NALI) initiatives, UTM-MOOCs incorporated Blended Learning as an approach to complement the traditional teaching and learning methods in higher learning institution. Blended learning is a growing instructional trend, and based on this approach, the course is delivered in a partly online format, where the material is often presented in a way that encourages asynchronous learning. Refer to this blended learning approach, this study was adopted one-group pretest-posttest design to examine students’ perception of integrating MOOCs for Research Methodology course.